Risk Factors for Synchronous Peritoneal Metastases in Colorectal Cancer: A Systematic Review and Meta-Analysis - Zhang, Yuanxin; Qin, Xiusen; Luo, Rui; Wang, Hui; Wang, Huaiming; Luo, Hongzhi (Frontiers in Oncology, 2022)
Background Early detection of synchronous colorectal peritoneal metastases (CPMs) is difficult due to the absence of typical symptoms and the low accuracy of imaging examinations. Increasing the knowledge of the risk factors for synchronous CPM may be essential for early diagnosis and improving their management. This study aimed to identify the risk factors for synchronous CPM. Method The study was registered at PROSPERO (CRD42020198548). The PubMed, Embase and Cochrane Library databases were searched for studies comparing the clinicopathological and molecular features between patients with or without synchronous CPM. The pooled data were assessed by a random-effects model. Results Twenty-five studies were included. A synchronous CPM was positively associated with female sex (OR 1.299; 1.118 to 1.509; P = 0.001), PROK1/PROKR2-positivity (OR 2.244; 1.031 to 4.884; P = 0.042), right-sided colon cancer (OR 2.468; 2.050 to 2.970; P < 0.001), poorly differentiated grade (OR 2.560; 1.537 to 4.265; P < 0.001), BRAF mutation (OR 2.586; 1.674 to 3.994; P < 0.001), mucinous adenocarcinoma (OR 3.565; 2.095 to 6.064; P < 0.001), signet-ring cell carcinoma (OR 4.480; 1.836 to 10.933; P = 0.001), N1-2 (OR 5.665; 3.628 to 8.848; P < 0.001), T4 (OR 12.331; 7.734 to 19.660; P < 0.001) and elevated serum CA19-9 (OR 12.868; 5.196 to 31.867; P < 0.001). Conclusions These evidence-based risk factors are indicators that could predict the presence of synchronous CPMs and can improve their management. Systematic Review Registration www.crd.york.ac.uk/prospero, identifier: CRD42020198548.